Implementation of Room Service E-Module on Food and Beverage Service Subject for Vocational High School Students of Hospitality Expertise Competency (Journal of Vocational and Career Education, 2022)
Due to the implementation of Large-Scale Social Restrictions (PSBB) caused by Covid-19 pandemic, the learning process has been switched to be online. Eleventh grade vocational high school students of the hospitality skill competency experience difficulties and limitations in the online learning process. Therefore, students need learning media that are in accordance with the situation and conditions, and effectively improve competence, namely Android-based e-module. This study aims to develop, analyze the feasibility, and analyze the effectiveness of the Room Service E-Modul. The research method used is Research and Development with ADDIE approach and quantitative method with an experimental two group design approach. This study involved three media expert validators and three material expert validators. The implementation of e-modules is carried out in online learning for 4 x 3 x 45 minutes. The data collection techniques used were needs analysis observation, e-module feasibility test questionnaire, and pretest and posttest. Analysis of the data used in this study is the mean, descriptive analysis of the percentage, N-Gain, and independent t-test. The results showed that: 1) the results of the Room Service E-Module feasibility test got an average value of 3.33 in the very feasible category; 2) E-module room service is declared effective in increasing the competence of students with an average N-gain of 0.71 in the high category, with a significant value of p = 0.000.